2012
DOI: 10.1038/nnano.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure to polystyrene nanoparticles affects iron absorption

Abstract: The use of engineered nanoparticles in food and pharmaceuticals is expected to increase, but the impact of chronic oral exposure to nanoparticles on human health remains unknown. Here, we show that chronic and acute oral exposure to polystyrene nanoparticles can influence iron uptake and iron transport in an in vitro model of the intestinal epithelium and an in vivo chicken intestinal loop model. Intestinal cells that are exposed to high doses of nanoparticles showed increased iron transport due to nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
186
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(200 citation statements)
references
References 43 publications
6
186
2
6
Order By: Relevance
“…Similar results were obtained from the intestinal loop model of the chicken, where acute exposure resulted in lower iron absorption than in chronically exposed chickens. Acute oral exposure to nanoparticles disrupted the iron transport, whereas chronic exposure to high doses of nanoparticles increased the iron transport and iron absorption by increasing the surface area of the intestinal lumen available for iron absorption by remodelling the intestinal villi [7]. This study provides valid evidence for the increase in absorption of molecules when the gastrointestinal tract is exposed to nanoparticles and can be exploited to increase the bioavailability of nutrients and drugs that are administered orally.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar results were obtained from the intestinal loop model of the chicken, where acute exposure resulted in lower iron absorption than in chronically exposed chickens. Acute oral exposure to nanoparticles disrupted the iron transport, whereas chronic exposure to high doses of nanoparticles increased the iron transport and iron absorption by increasing the surface area of the intestinal lumen available for iron absorption by remodelling the intestinal villi [7]. This study provides valid evidence for the increase in absorption of molecules when the gastrointestinal tract is exposed to nanoparticles and can be exploited to increase the bioavailability of nutrients and drugs that are administered orally.…”
Section: Introductionmentioning
confidence: 66%
“…When the drugs were reduced to a size of 280 nm by pearl milling, their bioavailability was much higher than that of the micro-sized counterparts [6]. Mahler et al [7] showed that oral exposure to polystyrene nanoparticles affected iron uptake and absorption through in vivo studies in chickens and in vitro studies in Caco-2 and HT29/MTX cell lines. High doses of nanoparticles caused the disruption of the cell membranes and CONTACT Shivendu Ranjan shivenduranjan@gmail.com; shivendu@vit.ac.in increased the iron transport through them.…”
Section: Introductionmentioning
confidence: 99%
“…Because a large proportion of nanoparticles penetrate the lung periphery, i.e., the alveolar region, particles deposited in the alveoli are readily transferred to the blood and are then quickly dispersed throughout the human body, including infants (Hinds, 1999;Bolch et al, 2001;Semmler-Behnke et al, 2012). Furthermore, at least one report on the effect that oral exposure to nanoparticles has on the human body, has determined that all kind of nanoparticle behavior in the environment could be issues that should be investigated (Mahler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…12 Our in vitro experiments show that 50 lm polystyrene, carboxylated, spherical particles are transported via a paracellular, non-energy-dependent process while 200 nm particles of the same material transport are transported across the in vitro GI tract through an energy-dependent process such as within cellular vesicles. When nanoparticles are present at moderate concentrations iron transport is inhibited, potentially making an individual go from an ironsufficient to an iron-deficient diet.…”
Section: Living Cell Models Of Humansmentioning
confidence: 75%
“…Our most realistic tissue construct is the GI tract which contains cell lines that mimic three cell types in appropriate ratios. [12][13][14] A major component of the current call for proposals from DARPA, NIH, and DTRA is for more biologically authentic tissues. Colleagues with in-depth expertise in tissue engineering have much to contribute in this regard.…”
Section: Living Cell Models Of Humansmentioning
confidence: 99%